Risk of Suicidal Behavior With Use of Efavirenz: Results from the Strategic Timing of Antiretroviral Treatment Trial. (12th March 2018) - Arenas-Pinto, Alejandro; Grund, Birgit; Sharma, Shweta; Martinez, Esteban; Cummins, Nathan; Fox, Julie; Klingman, Karin L; Sedlacek, Dalibor; Collins, Simon; Flynn, Patricia M; Chasanov, William M; Kedem, Eynat; et al.
Abstract: Background: Randomized trials have shown increased risk of suicidality associated with efavirenz (EFV). The START (Strategic Timing of Antiretroviral Treatment) trial randomized treatment-naive human immunodeficiency virus (HIV)–positive adults with high CD4 cell counts to immediate vs deferred antiretroviral therapy (ART). Methods: The initial ART regimen was selected prior to randomization (prespecified). We compared the incidence of suicidal and self-injurious behaviours (suicidal behavior) between the immediate vs deferred ART groups using proportional hazards models, separately for those with EFV and other prespecified regimens, by intention to treat, and after censoring participants in the deferred arm at ART initiation. Results: Of 4684 participants, 271 (5.8%) had a prior psychiatric diagnosis. EFV was prespecified for 3515 participants (75%), less often in those with psychiatric diagnoses (40%) than without (77%). While the overall intention-to-treat comparison showed no difference in suicidal behavior between arms (hazard ratio [HR], 1.07, P = .81), subgroup analyses suggest that initiation of EFV, but not other ART, is associated with increased risk of suicidal behavior. When censoring follow-up at ART initiation in the deferred group, the immediate vs deferred HR among those who were prespecified EFV was 3.31 ( P = .03) and 1.04 ( P = .93) among those with other prespecified ART; ( P = .07 for interaction). In the immediate group, the risk was higher among those with prior psychiatric diagnoses, regardless of prespecified treatment group. Conclusions: Participants who used EFV in the immediate ART group had increased risk of suicidal behavior compared with ART-naive controls. Those with prior psychiatric diagnoses were at higher risk. Abstract : We compared the incidence of suicidal behavior between human immunodeficiency virus–positive adults with high CD4 count started on antiretroviral therapy immediately or after CD4 count fell below 350 cell/mL. Participants started on efavirenz-based, but not other combinations, had increased risk of suicidal behavior.